CONSTITUTION. (The Accounting Review, 1928)
Abstract This article provides information about the constitution of the Accounting Association of the U.S. In the article 1, it is written that the name of the organization shall be The American Association of University Instructors in accounting. Second article is about the objects of the Association which shall be as follows, to further the advancement of education in accounting, particularly the development and refinement of the theory of accounting, content of accounting courses, and methods of instruction. To encourage practical research in accounting, especially theory and methods, the interpretation of accounting data, and the use of accounting statistics in related fields. Article 3 is about the membership of the association. Active membership shall be limited to those engaged in giving instruction in accounting in educational institutions of collegiate rank. Other persons interested in instruction in accounting may become associate members. Any active member who permanently discontinues his teaching work as aforesaid thereby shall become an associate member. Any associate member who undertakes teaching work as aforesaid shall thereby become an active member.